The Influence of Tutor Methods, Facilities, Independence, and Motivation on UPPBJ-UT Makassar Students’ Outcomes in UPPBJ-UT Makassar - Muh Alwi; Kusmaladewi Kusmaladewi; Juhardi Juhardi; Risnashari Risnashari; Jalil Jalil; Arifin Tahir (International Journal of Educational Development, 2025)
The purpose of the study was to obtain an overview of how the influence of tutor teaching methods, tutorial facilities, achievement motivation and learning independence, on learning outcomes both partially and simultaneously. This research uses quantitative method with ex pos facto approach. The data was collected using a questionnaire with a Likert scale of 1-4, the sampling method was random sampling, to determine the sample size using the Harry King nomogram with an error rate of 1% with a multiple factor of 99%, namely 1.573 so that a sample of 78 respondents was obtained. The collected data were analysed with parametric statistics of multiple regression test with the help of SPSS IBM 23. The results of the study found that. Tutor teaching methods, significantly affect student learning outcomes at UPPJB-UT Makassar. Tutorial facilities, have a significant effect on student learning outcomes at UPPJB-UT. Learning independence has a significant effect on student learning outcomes at UPPJB-UT Makassar. Achievement motivation has a significant effect on student learning outcomes at UPPJB-UT Makassar. Tutor teaching methods, tutorial facilities, learning independence and achievement motivation simultaneously affect student learning outcomes at UPPJB-UT Makassar.